Metodyka zarządzania procesowego w organizacjach gospodarczych - Kafel, Tomasz (Methodology of business process management in enterprises, 2005)
In the first part of article the essence and origin of Business Process Management (BPM) are presented. The factors of BPM development and methods on the base it originates are indicated. The comparison of BPM and functional management is analyzed there. Further on the authors characterizes selected methodologies of BPM, including his own proposition. At the end of the paper, description of the rules and approaches of BPM implementation into business practice is shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 261-269